PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA PESERTA DIDIK KELAS V SD N 01 WAY EMPULAU ULU - RENDY RINALDY SAPUTRA; LIYAN DESI YULIA (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2019)
This research was motivated by the low achievement of fifth grade students at SD N 01 Way Empulau Ulu on science subjects. Based on observations, the low scores of students are due to the lack of learning activities with good learning methods. Therefore, researchers are interested in conducting research related to learning methods with the cooperative model Teams Games Tournament (TGT) in order to improve student achievement in science subjects. This study aims to see whether the application of the Teams Games Tournament (TGT) method can bind the achievements of fifth grade students of SD N 01 Way Empulau Ulu on science subjects. The method used in this study is the Classroom Action Research (CAR) method with the hypothesis: The application of the cooperative learning model of the Teams Games Tournament (TGT) type can improve the science learning achievement of fifth grade students at SD N 01 Way Empulau Ulu. Based on observations and analysis of data, it can be concluded several things including: 1) Application of the Cooperative Learning Model Type Teams Games Tournament (TGT) can improve the learning achievement of fifth grade students at SD N Way Empulau Ulu. 2) There is an increase in student learning achievement from cycle I to cycle II by 15%. Keywords : Teams Games Tournament (TGT), student achievement, Science.